ENERGI EXPENDITURE PADA LANSIA - Yuniar Rosmalina; Dewi Permaesih; Fitrah Emawati; Reviana Christiani; Susilowati Herman (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2002)
ENERGY EXPENDITURE OF ELDERLY PEOPLE.Background: Physical activity is a factor to estimate the energy requirement. The elderly tend to reduce their activities which influence their energy requirement. Now aday the energy need for elderly is extrapolated from the adult. Energy expenditure based on their daily activities Is a method to estimate the energy requirement.Objectives: The purpose of the study was to assess energy expenditure of elderly people based on the daily physical activities.Methods: The study was conducted in 2 sub-sub districts of Bogar Country. A total of 92 elderly (42 men and 50 women) were included in this study. The inclusion criteria were BMI 18.5- 25.0, physically and hematologically healthy and agree to participate in this study. Physical activities data were collected 3 days respectively using method record and recall and energy intakes using 3 day food record by weighing.Results: The average age was 67.5 ± 5,1 years for male elderly and 65.4 ± 3.9 years of female elderly. Recreational activities (reading, watching TV, sitting) were the most activities done by male elderly (34.9% of the day) while female elderly 34.8% of the day were spent for sleeping activity. The highest energy expenditure of male elderly was contributed from reactional activities (570.3 ± 187.8) Kcal/day while female elderly the highest energy expenditure was contributed from household work activities. The average energy expenditure for male elderly was 1870.2 ± 261.2 Kcal/day or 34.4 Kcal/Body weight/day and female elderly was 1840.2 ± 255.7 Kcal/day or 38.2 Kcal/Body weight/day. The energy Intake of male elderly was 1858 ± 471.7 Kcal/day or 34.1 Kcal/Body weight/day and female elderly was 1472 ± 255.7 Kcal/day or 30.8 Kcal/Body weight/day.Conclusions: Conclusion of this research was the energy expenditure of male elderly balance with their energy consumption, while the energy expenditure of female elderly higher than their energy consumption.Recommendations: Further study on physical activities of elderly of different culture in Indonesia is needed.Keywords: elderly, physical activities, energy expenditure